Cellular response and extracellular vesicles characterization of human macrophages exposed to fine atmospheric particulate matter. (November 2019) - Martin, Perrine J.; Héliot, Amélie; Trémolet, Gauthier; Landkocz, Yann; Dewaele, Dorothée; Cazier, Fabrice; Ledoux, Frédéric; Courcot, Dominique
Abstract: Exposure to fine atmospheric Particulate Matter (PM) is one of the major environmental causes involved in the development of inflammatory lung diseases, such as chronic obstructive pulmonary disease (COPD) or asthma. When PM is penetrating in the pulmonary system, alveolar macrophages represent the first line of defense, in particular by triggering a pro-inflammatory response, and also by their ability to recruit infiltrating macrophages from the bone marrow. The aim of this in vitro study was to evaluate the gene expression and cytokine production involved in the toxicological and inflammatory responses of infiltrating macrophages, as well as the Extracellular Vesicles (EVs) production, after their exposure to PM. The ability of these EVs to convey information related to PM exposure from exposed macrophages to pulmonary epithelial cells was also evaluated. Infiltrating macrophages respond to fine particles exposure in a conventional manner, as their exposure to PM induced the expression of Xenobiotic Metabolizing Enzymes (XMEs) such as CYP1A1 and CYP1B1, the enzymes involved in oxidative stress SOD2, NQO1 and HMOX as well as pro-inflammatory cytokines in a dose-dependent manner. Exposure to PM also induced a greater release of EVs in a dose-dependent manner. In addition, the produced EVs were able to induce a pro-inflammatory phenotype on pulmonary epithelial cells, with the induction of the release of IL6 and TNFα proinflammatory cytokines. These results suggest that infiltrating macrophages participate in the pro-inflammatory response induced by PM exposure and that EVs could be involved in this mechanism. Graphical abstract: Image 1 Highlights: Infiltrating macrophages respond conventionally to PM2.5. Exposure of infiltrating macrophages to PM2.5 -0.3 induces a greater release of EVs in a dose-dependent manner. EVs produced by PM2.5-0.3 exposed macrophages are able to induce a pro-inflammatory phenotype on pulmonary epithelial cells.